Ten-year results of hypofractionated whole breast radiotherapy and intraoperative electron boost in premenopausal women. (December 2022) - Leonardi, Maria Cristina; Cormio, Chiara Fausta; Frassoni, Samuele; Dicuonzo, Samantha; Fodor, Cristiana; Intra, Mattia; Zerella, Maria Alessia; Morra, Anna; Cattani, Federica; Comi, Stefania; Fusco, Nicola; Zaffaroni, Mattia; et al.
Highlights: Boost dose is beneficial for young patients affected by breast cancer. Intraoperative electrons (IOERT) boost and hypofractionated whole breast irradiation (HWBI) represent a suitable modality. Local control with IOERT/HWBI was excellent, even in very young patients. High tumor bed fibrosis was observed due to high cumulative EQD2 boost dose. Abstract: Aim: To evaluate outcome of intraoperative electron boost (IOERT) and hypofractionated whole breast irradiation (HWBI) for breast cancer (BC) in young women. Methods and Materials: Women aged ≤ 48 with pT1-2 N0-1 BC received 12 Gy IOERT boost during conservative surgery followed by 3-dimensional conformal HWBI in 13 fractions (2.85 Gy/die). Local relapses (LR) and survival (disease-free, DFS; specific, BCSS; overall, OS) were analyzed. Results: 481 consecutive BC patients, mostly node negative, with median age of 42 were treated between 2004 and 2014. Median tumor size was 1.48 cm and median IOERT collimator was 4 cm. After 25-day mean interval, HWBI was delivered. At a median follow-up of 9.6 years, there were 23 LRs (4.8 %, 9 of which were in the boost region). Ten-year LR cumulative incidence was 4.1 % (95 %CI, 2.5–6.3). Over time, local control rate decreased for Luminal A and HER2 positive with negative hormonal receptors, while remained steady for triple negative. At multivariate analysis, LR predictors included age < 40, extensive intraductal component and the use of 4-cm IOERT collimator size. Ten-year survival outcomes were as follows: DFS 80.0 % (95 % CI, 75.8–83.5), BCSS 97.5 % (95 % CI, 95.5–98.6 %), OS 96.5 % (95 % CI, 94.3–97.9). Luminal B HER2 negative had the worse survival outcomes. Perioperative complications were uncommon (16.4 %), acute toxicity was mild (<2% Grade 3), but moderate/severe fibrosis was described in 40.8 % of the cases. Cosmesis was scored as excellent/good in 86 % of the cases. Conclusions: ELIOT boost and HWBI achieved an excellent local control at the cost of tumor bed fibrosis. IOERT boost dose lower than 12 Gy is advisable.